Nux vomica, the Arnica of Recovery from Addiction: An Exploratory Study of the Use of Homeopathy in the Reduction of Post–Acute Withdrawal Syndrome in Addiction Treatment - Butehorn, Loretta; Gumz, Peris; Randolph, Leah (Homœopathic Links, 2015)
Clients coming out of traditional medical detoxification often experience post–acute withdrawal syndrome, symptoms of significant cravings for drugs, as well as mental, emotional and physical symptoms of protracted withdrawal. This article details a protocol of using Nux vomica in three American treatment settings, with data indicating a positive impact on both immediate symptoms and long-term stabilisation in treatment. Consistently in all three groups, those who chose to use homeopathy completed substance abuse treatment programs at a higher rate than those who did not. The authors conclude that the role of homeopathy for recovery from addiction merits further investigation.
Keywords: Addiction; Detox; Genus Epidemicus; Nux vomica; Post–acute withdrawal syndrome; Alcohol and drug treatment